Analisis Dana Investasi dan Biaya Pertanggungan terhadap Pendapatan Asuransi Jiwa Syariah - Fitri Rorizki; Yenni Samri Juliati Nasution (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Sharia insurance investment funds consist of money donated by participants and deposited into the tabarru fund by the fund manager, namely the insurance business. Part of the participants' investment funds will be invested in sharia securities that are guaranteed to be halal. The sum insured is the entire amount of money that will be issued or paid by the insurer (insurance company). When the insured (policyholder) submits a claim according to the risk promised in the policy agreement or insurance program, the money is disbursed. This study intends to determine the effect of investment funds and coverage costs on sharia life insurance income at Bumiputera Syariah Life Insurance. This research is a quantitative research that uses secondary data as a data source. Using Eviews version 9, conventional assumption tests and hypothesis tests were used for data analysis. According to the findings of the study, both the variable investment funds and coverage costs have a large impact on Islamic life insurance income. Keywords: Investment fund, cover cost, Insurance Income, Islamic Insurance